Biopolitics, geopolitics, life settler states and indigenous presence - Dietrich, René 1978-; Knopf, Kerstin 19XX- (Duke University Press, 2023)
The contributors to Biopolitics, Geopolitics, Life investigate biopolitics and geopolitics as two distinct yet entangled techniques of settler colonial states across the globe, from the Americas and Hawai'i to Australia and Aotearoa/New Zealand. Drawing on literary and cultural studies, social sciences, political theory, visual culture, and film studies, they show how biopolitics and geopolitics produce norms of social life and land use that delegitimize and target Indigenous bodies, lives, lands, and political formations. Among other topics, the contributors explore the representations of sexual violence against Native women in literature, Indigenous critiques of the carceral state in North America, Indigenous Elders' refusal of dominant formulations of aging, the governance of Indigenous peoples in Guyana, the displacement of Guaraní in Brazil, and the 2016 formal acknowledgement of a government-to-government relationship between the US federal government and the Native Hawaiian community. Throughout, the contributors contend that Indigenous life and practices cannot be contained and defined by the racialization and dispossession of settler colonialism, thereby pointing to the transformative potential of an Indigenous-centered decolonization.Contributors. René Dietrich, Jacqueline Fear-Segal, Mishuana Goeman, Alyosha Goldstein, Sandy Grande, Michael R. Griffiths, Shona N. Jackson, Kerstin Knopf, Sabine N. Meyer, Robert Nichols, Mark Rifkin, David Uahikeaikaleiʻohu Maile
Keywords: SOCIAL SCIENCE / Indigenous Studies; Biopolitics; Decolonization; Geopolitics; Indigenous peoples -- Colonization; Settler colonialism; Aufsatzsammlung